FORMULA DEVELOPMENT OF FREEZED DRIED RIFAMPICIN-LOADED CHITOSAN-ACEMANNAN- MODIFIED-LIPID NANOPARTICLES AND INTRACELLULAR STAPHYLOCOCCUS AUREUS ANTI- MICROBIAL ACTIVITY STUDY ON LUNG EPITHELIAL CELLS - Juniatik, Meta
Infectious disease is one of the threats to human health that continues to grow from low severity to death. Microbes always try to adapt to environment and present resistance mechanisms to available antibiotics. Staphylococcus aureus (S. aureus) is one of the microbes that can be internalized into cells and prevent the host's immune system. The development of antibiotic delivery systems to transport host cells is needed to increase the effectiveness of therapy and prevent its resistance. Rifampicin is one of the active substances that has activity against S. aureus infection but has limited intracellular penetration and stability. This study aims to formulate rifampicin into powdered lipid nanoparticles to improve the stability during storage and cellular penetration. The drying process was carried out by freeze-drying method with the addition of glucose and trehalose cryoprotectants at certain concentrations. The stability of the formula was evaluated by analyzing the particle size for 2 months. The antimicrobial activity of the formula was analyzed by counting the number of intracellular colonies using the ALT method after administration of lipid nanoparticles to A549 lung epithelial cells infected with S. aureus. The extent of intracellular antimicrobial activity was also confirmed by confocal microscopy and viability testing. The addition of 5% glucose cryoprotectant to the acemannan-chitosan-conjugated lipid nanoparticles resulted in a dry powder with a particle size of 340.2+38.11 nm, polydispersity index of 0.264+0.034, zeta potential of -25.77±0.384 mV and no significant change in particle size for 2 months. The cryoprotectant played an important role in maintaining the stability of lipid nanoparticles. The extracellular antimicrobial activity test showed that there was no difference in the inhibitory power between the freeze-dried formula of lipid nanoparticles with rifampin solution and unlyophilized rifampin NLC. The formula treated to A549 cells did not show any toxicity. The formula was able to provide intracellular antimicrobial activity at a concentration of 20 g/ml. The inhibition of intracellular colonies was 90%, confirmed by the presence of intracellular S. aureus death on confocal microscopy observation and relatively higher cell viability than unmodified lipid nanoparticles.